Sequence stratigraphic analysis for hydrocarbon prospectivity of the Kamta structure in the foredeep region of the Bengal Basin - Lima Akter Choiti; A.S.M. Woobaidullah; Shakhawat Hossain (Heliyon)
Seismic sequence stratigraphic analysis is a powerful technique for understanding the architecture and geometry of hydrocarbon reservoirs and identifying new exploration leads in mature fields. This study applies sequence stratigraphic analysis to the Kamta and Rupganj gas fields in the Bengal Basin, aiming to refine the understanding of their stratigraphic architecture and evaluate their exploration potential. Wireline logs and 2D seismic data were integrated to identify depositional facies, delineate seismic sequences, and detect hydrocarbon prospects. The analysis identified four primary depositional facies: progradational shoreface (funnel-shaped coarsening-upward facies), retrogradational shoreface (bell-shaped fining-upward facies), channel fill (cylindrical-shaped aggradational facies), and regressive to transgressive shoreface transitions (symmetrical facies). Ten seismic sequences were mapped, bounded by sequence boundaries and maximum flooding surfaces, with most sequences comprising Lowstand Systems Tract (LST), Transgressive Systems Tract (TST), and Highstand Systems Tract (HST). Sequences 1 and 2 exhibit significant deltaic progradation (∼9 km southeastward), while the stratigraphic interval above sequence 11 reflects fluvial deposition dominated by coarse-grained sandstones and intense channelization. Depth maps show southeastward thickening of sequence boundary 1 and northeastward thickening for subsequent boundaries, with sand-shale alternations dominating the lithology. Seismic amplitude analyses identified promising hydrocarbon leads beneath the Kamta-1 well, highlighting favorable reservoir-seal configurations. These findings provide a robust understanding of the stratigraphic architecture and depositional history of the reservoirs in Kamta and Rupganj gas fields, offering critical insights for future exploration and development in the Bengal Basin.